The Interrelationship of Store Atmosphere and Price of Goods in Consumer Purchasing Decisions - Netty Dyan Prastika; Jecyka Tri Putri Andiska (Politeknik Negeri Bengkalis, 2022)
Demands from customers can influence the decision of making a preeminent purchase of goods. The high, low interest rates for customers can be seen from purchasing decisions that have to do with the price and the mood of the store. This can influence customers to become interested in an item because it is backed up by an affordable price and the shop atmosphere that correspond to what is sold. This study aims to determine the influence of shop atmosphere and price on purchasing decisions Polo Milano brand at Big Mall Samarinda. The subjects of this study were 120 customers who were selected using simple random sampling technique. The data collection method used is a scale of store atmosphere, price, and purchasing decisions. The collected data were analyzed using multiple regression analysis with the help of the Statistical Package for Social Sciences (SPSS) 26.0 for mac Os program. The results showed that: (1) there was a significant effect of store atmosphere and price on purchasing decisions for visitors to Big Mall Samarinda and customers of the Polo Milano Big Mall Samarinda brand with F count = 38,187 > F table = 3.07 and p value = 0.000 and have the influence contribution (R2) is 3.99%; (2) there is no significant effect of store atmosphere on purchasing decisions for visitors to Big Mall Samarinda and customers of the Polo Milano Big Mall Samarinda brand with a coefficient of beta (β) = 0.116, t count = 1.498 < t table = 1.980, and p = 0.137 (p > 0.05); (3) there is a significant price effect on purchasing decisions for visitors to Big Mall Samarinda and customers of the Polo Milano Big Mall Samarinda brand with a coefficient of beta (β) = 0.578, t count = 7,448 < t table = 1,980, and p = 0.000 (p < 0.05).